(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This study, prepared in the IMRAD format, presents a comparative institutional and financial analysis of the post-investment sustainability of infrastructure projects financed by the Asian Development Bank (ADB) and the World Bank (WB) in Central Asia. The relevance of the study is determined by the fact that Uzbekistan annually attracts USD 1–2 billion in loan resources from the WB and ADB for infrastructure development; however, mechanisms for long-term management of the assets created under such projects often remain a weak link. Based on Project Performance Evaluation Reports (PPER) and Implementation Completion and Results Reports (ICR) for 2015–2023, 42 projects in water supply, energy, and road infrastructure were analyzed. The study introduces the Asset Management Sustainability Index (AMSI). The results reveal a “donor paradox”: physical construction is successfully completed in 88% of cases, yet the financial sustainability of assets through tariffs and OPEX is achieved in only 31% of ADB projects and 42% of WB projects. The Discussion section substantiates the need to move from “project management” to “lifecycle asset management” within loan agreements.